2014
DOI: 10.1194/jlr.r046441
|View full text |Cite
|
Sign up to set email alerts
|

Improved methodologies for the study of adipose biology: insights gained and opportunities ahead

Abstract: greater caution must be taken in interpreting studies of adipogenesis and adipocyte metabolism.In this review, we offer a consolidated view of the wideranging approaches that can be taken to study adipose biology and discuss important considerations and pitfalls associated with each method. We divide the discussion into three sections; the fi rst section describes model systems, ways to understand where and when molecules of interest may play a role in the adipose lineage, and recent insights gained from these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 216 publications
(258 reference statements)
0
57
0
Order By: Relevance
“…The recent development of new genetic lineage tracing systems have now led to a better understanding of how the individual adipose depots expand in mice during obesity (Wang et al, 2014a). Scherer and colleagues developed an elegant “pulse-chase” lineage-tracing model, termed the “AdipoChaser” mouse (Wang et al, 2013).…”
Section: Physiological Recruitment Of Adipocytes In Adults: Links Tomentioning
confidence: 99%
“…The recent development of new genetic lineage tracing systems have now led to a better understanding of how the individual adipose depots expand in mice during obesity (Wang et al, 2014a). Scherer and colleagues developed an elegant “pulse-chase” lineage-tracing model, termed the “AdipoChaser” mouse (Wang et al, 2013).…”
Section: Physiological Recruitment Of Adipocytes In Adults: Links Tomentioning
confidence: 99%
“…Adipocytes are formed early in life and the number of adipocytes does not generally increase in lean adults. However, it is possible for precursor cells to differentiate into adipocytes in adults when the demand for energy storage increases (Wang et al, 2014). Paraben-enhanced differentiation would supplement this process and increase the prevalence of obesity within exposed populations.…”
Section: Introductionmentioning
confidence: 99%
“…3H ). Obesity is associated with an overall increase in expression of several collagens that results in fi brotic state ( 28,29 ). Then, we tested mRNA levels of several fi brosis-related genes, and found that Col1a1 , Col3a1 , Col6a1 , and Elastin were upregulated ( Fig.…”
Section: Nrx Overexpression Leads To Adipocyte Hypertrophy Combined Wmentioning
confidence: 98%